Technology of ultra-high temperature inner shell protective layer for inner wall of glass furnace

By applying ceramic materials mixed with lanthanide rare earth oxides and oxides to the inner wall of the glass kiln, the problem of traditional refractory materials falling off at high temperatures is solved, the high temperature stability and durability of the ceramic protective layer are achieved, and the kiln is extended Service life and improve productivity.

CN118561503BActive Publication Date: 2024-12-24DEZHOU JINGHUA YAOYONG GLASS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411059707.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-05
Publication Date
2024-12-24
Estimated Expiration
2044-08-05

AI Technical Summary

Technical Problem

Traditional refractory materials such as zirconium corundum bricks and magnesium bricks fall off layer by layer under the continuous erosion of high-temperature glass liquid, resulting in changes in the composition of the glass liquid, affecting the quality of glass products and shortening the service life of the kiln.

Method used

Using ceramic materials incorporated with trace amounts of lanthanide rare earth oxides and oxides, a ceramic protective layer with high stability and durability in extremely high temperature environments is formed through multi-layer coating and optimization of the kiln procedure.

Benefits of technology

It significantly improves the high temperature stability and durability of ceramic materials, extends the service life of the kiln, reduces maintenance frequency, improves production efficiency, and maintains stability and integrity in complex chemical reaction environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118561503B_ABST
    Figure CN118561503B_ABST
Patent Text Reader

Abstract

The present application relates to the field of glass production, and discloses a process for the ultra-high temperature inner shell protective layer of the inner wall of a glass kiln, which includes the following steps: material preparation: preparing a ceramic material doped with trace amounts of lanthanide rare earth oxides and eye oxides, applying ceramic material: evenly applying a layer of the above ceramic material with a thickness of about one centimeter on the surface of the inner cavity of the kiln, first kiln baking: preheating at 800 degrees for 24 hours, heating at 1200 degrees for 12 hours, high-temperature baking at 1580 degrees for 72 hours, and low-temperature baking at 800 degrees for 12 hours, cooling and secondary kiln baking: after cooling the kiln to 200 degrees, preheating at 800 degrees for 24 hours, heating at 1200 degrees for 12 hours, and high-temperature baking at 1450 degrees for 72 hours are performed, and formal production: after the secondary kiln baking is completed, glass raw materials are added to enter the formal production stage. By adding lanthanide rare earth oxides and eye oxides, the high-temperature stability and durability of ceramic materials are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of glass production, in particular to a process for forming an ultra-high temperature protective inner shell layer on the inner wall of a glass furnace. Background Art

[0002] With the popularity of large-area touch-screen electronic products such as smart phones and tablets, consumers have higher requirements for the anti-destructive performance of display screens, such as impact resistance, drop resistance, and scratch resistance. For this reason, major terminals are constantly updating screen protection materials. Glass is used in the field of screen protection with its excellent transparency, hardness, corrosion resistance, and easy processing and molding. In the production process of glass products, the glass kiln needs to operate in a high-temperature and high-corrosion environment of about 1500 degrees.

[0003] Although traditional refractory materials such as zirconium corundum bricks and magnesium bricks can resist high temperatures to a certain extent, they will still fall off layer by layer under the continuous erosion of high-temperature glass liquid, causing changes in the composition of the glass liquid and affecting the quality of glass products, such as "unstable material color, sand, bubbles" and other problems. At the same time, the shedding of refractory materials will also accelerate the aging of the kiln and shorten its service life.

[0004] In view of the above-mentioned deficiencies of the prior art, the present invention provides an improved process for preventing ultra-high temperature inner shell protective layer of the inner wall of a glass furnace. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a process for forming an ultra-high temperature inner shell protective layer on the inner wall of a glass kiln, which solves the problem that although traditional refractory materials such as zirconium corundum bricks and magnesium bricks can resist high temperatures to a certain extent, they will still fall off layer by layer under the continuous scouring of high-temperature molten glass, causing changes in the composition of the molten glass and affecting the quality of glass products.

[0006] To achieve the above purpose, the present invention is implemented by the following technical scheme: The process of the ultra-high temperature inner shell protective layer on the inner wall of the glass furnace comprises the following steps:

[0007] Material preparation: preparing a ceramic material doped with trace amounts of lanthanide rare earth oxides and oxides;

[0008] Apply ceramic material: Apply a layer of the above ceramic material with a thickness of about one centimeter evenly on the surface of the inner cavity of the kiln;

[0009] Initial kiln baking: 24 hours of preheating at 800 degrees, 12 hours of heating at 1200 degrees, 72 hours of high-temperature baking at 1580 degrees, and 12 hours of low-temperature baking at 800 degrees;

[0010] Cooling and secondary kiln baking: After the kiln is cooled to 200 degrees, it is preheated at 800 degrees for 24 hours, heated at 1200 degrees for 12 hours, and baked at 1450 degrees for 72 hours;

[0011] Formal production: After the second kiln baking is completed, glass raw materials are added to enter the formal production stage.

[0012] Preferably, the amount of the lanthanide rare earth oxide added is 0.5% to 2% of the total weight of the ceramic material, and the amount of the oxide added is 1% to 3% of the total weight of the ceramic material.

[0013] Specifically, the types of lanthanum series rare earth oxides in the ceramic material include lanthanum oxide, cerium oxide and praseodymium oxide, and the primary oxide is titanium oxide.

[0014] Preferably, main components of the ceramic material are aluminum oxide, zirconium oxide and magnesium oxide, and in the step of applying the ceramic material, the thickness of the ceramic material is 0.5 cm to 1.5 cm.

[0015] Specifically, the content of aluminum oxide is 50% to 70%, the content of zirconium oxide is 20% to 30%, and the content of magnesium oxide is 10% to 20%.

[0016] Preferably, in the high-temperature baking step of the initial kiln baking, the temperature range is 1550 degrees to 1600 degrees, and in the low-temperature baking step of the initial kiln baking, the temperature range is 750 degrees to 850 degrees.

[0017] Specifically, the temperature should be raised slowly in stages during the high-temperature roasting phase to avoid uneven heating of the ceramic material and the formation of cracks.

[0018] Preferably, in the high-temperature baking step of the secondary baking kiln, the temperature range is 1400 degrees to 1500 degrees, and in the cooling step, the cooling temperature range is 180 degrees to 220 degrees.

[0019] Specifically, the cooling step should control the cooling speed to avoid material cracking due to excessively rapid temperature changes.

[0020] Preferably, the ceramic material needs to be finely powdered before being applied, with a particle size range of 200 to 400 meshes. The ceramic material needs to be applied multiple times, with each application having a thickness of 0.2 cm to 0.5 cm.

[0021] Specifically, the interval between each application is 2 to 4 hours to ensure that each layer is fully dried and combined.

[0022] Preferably, the ceramic material needs to be naturally dried after being applied, and the drying time is 12 to 24 hours.

[0023] Specifically, natural drying should be carried out in a well-ventilated environment with a temperature of 20 to 30 degrees.

[0024] Preferably, in the preheating steps of the primary kiln baking and the secondary kiln baking, the preheating temperature ranges from 750 degrees to 850 degrees.

[0025] Specifically, the temperature should be raised evenly and slowly during the preheating phase to prevent an increase in the internal stress of the ceramic material due to a sudden temperature change.

[0026] Preferably, in the step of preparing the ceramic material, a binder needs to be added, and the type of the binder is sodium silicate or potassium silicate.

[0027] Specifically, the amount of the binder added is 3% to 5% of the total weight of the ceramic material, and is fully stirred during the mixing process.

[0028] Preferably, in the preparation step of the ceramic material, a high-temperature calcination treatment is required, and the calcination temperature ranges from 1300 degrees to 1500 degrees.

[0029] Specifically, the calcination time is 4 to 6 hours, and the material is slowly cooled after calcination to avoid cracks inside the material.

[0030] The present invention provides a process for forming an ultra-high temperature inner shell protective layer on the inner wall of a glass furnace. It has the following beneficial effects:

[0031] 1. The present invention significantly improves the high-temperature stability and durability of ceramic materials by adding lanthanide rare earth oxides and pyroxene oxides. Compared with traditional refractory bricks and general ceramic coatings, the materials of the present invention can still maintain excellent physical and chemical stability in extremely high temperature environments, ensuring that the inner wall of the kiln will not deform or crack during long-term high-temperature operation, thereby extending the service life of the kiln, reducing the maintenance and replacement frequency, and significantly improving production efficiency;

[0032] 2. The present invention utilizes lanthanum rare earth oxides such as lanthanum oxide, cerium oxide and praseodymium oxide to enhance the chemical corrosion resistance and oxidation resistance of ceramic materials. Compared with traditional materials, the ceramic coating of the present invention can effectively resist corrosion and oxidation in complex chemical reaction environments and oxidative environments, ensuring the stability and integrity of the material under harsh conditions. This feature enables the present invention to exhibit higher reliability and safety in various highly corrosive and oxidative glass production environments;

[0033] 3. The present invention significantly improves the thermal shock stability and mechanical strength of ceramic materials by optimizing material composition and multi-layer coating process. When the material undergoes rapid temperature changes, it can still maintain structural integrity without cracks or breaks. In addition, the high compressive strength of the material enables it to withstand the high mechanical stress and heavy pressure on the inner wall of the kiln, ensuring the structural stability and safe operation of the kiln. This superior thermal shock stability and mechanical strength greatly improves the reliability and sustainability of the kiln in high-frequency production, and reduces downtime and production costs caused by material damage. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1It is a flow chart of the present invention. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings of the present invention specification to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Please refer to the attached Figure 1 :

[0037] Example 1: Complex process for converting lanthanide rare earth oxides into lanthanum oxide

[0038] step:

[0039] Material preparation:

[0040] A ceramic material doped with 1% lanthanum oxide and 2% titanium oxide was prepared, and the main components were 60% aluminum oxide, 25% zirconium oxide, and 15% magnesium oxide.

[0041] The ceramic material is finely powdered to a particle size ranging from 200 to 400 meshes.

[0042] Add 3% sodium silicate as a binder and mix thoroughly.

[0043] The mixed material was calcined at 1300 degrees for 4 hours and then slowly cooled to room temperature.

[0044] Applying ceramic material:

[0045] Clean the inner surface of the kiln to ensure it is free of dust and oil.

[0046] Spread the ceramic material evenly on the inner cavity surface with a thickness of 1 cm.

[0047] After application, allow to dry naturally for 24 hours.

[0048] First time kiln baking:

[0049] Preheat at 800 degrees for 24 hours, slowly increase the temperature to avoid cracks.

[0050] Heating at 1200 degrees for 12 hours, maintaining uniform temperature rise.

[0051] 72 hours of high temperature grilling at 1580 degrees, with a temperature range of 1550 to 1600 degrees.

[0052] 12 hours of low temperature grilling at 800 degrees, with a temperature range of 750 to 850 degrees.

[0053] Cooling and secondary kiln baking:

[0054] The kiln is cooled to 200 degrees and the cooling rate is controlled.

[0055] Preheat at 800 degrees for 24 hours, slowly increase the temperature.

[0056] Heating at 1200 degrees for 12 hours, maintaining uniform temperature rise.

[0057] 72 hours of 1450 degree high temperature grilling, the temperature range is 1400 to 1500 degrees.

[0058] Official production:

[0059] After the second kiln baking is completed, glass raw materials are added to enter the formal production stage.

[0060] Summarize:

[0061] This embodiment utilizes lanthanum oxide and titanium oxide to improve the high temperature resistance and strength of the material, and is suitable for long-term production in a high-temperature glass furnace.

[0062] Example 2: Complex process of lanthanide rare earth oxide as cerium oxide

[0063] step:

[0064] Material preparation:

[0065] A ceramic material doped with 2% cerium oxide and 1% titanium oxide was prepared, and the main components were 50% aluminum oxide, 30% zirconium oxide, and 20% magnesium oxide.

[0066] The ceramic material is finely powdered to a particle size range of 300 meshes.

[0067] Add 4% potassium silicate as a binder and mix thoroughly.

[0068] The mixed material was calcined at 1400 degrees for 5 hours and then slowly cooled to room temperature.

[0069] Applying ceramic material:

[0070] Clean the inner surface of the kiln to ensure it is free of dust and oil.

[0071] Apply the ceramic material evenly on the surface of the inner cavity, with a thickness of 0.4 cm each time, and apply it multiple times to achieve a total thickness of 1.2 cm.

[0072] After application, allow to dry naturally for 12 hours.

[0073] First time kiln baking:

[0074] Preheat at 800 degrees for 24 hours, slowly increase the temperature to avoid cracks.

[0075] Heating at 1200 degrees for 12 hours, maintaining uniform temperature rise.

[0076] 72 hours of high temperature grilling at 1570 degrees, the temperature range is 1550 degrees to 1570 degrees.

[0077] 12 hours of low temperature grilling at 800 degrees, with a temperature range of 750 to 850 degrees.

[0078] Cooling and secondary kiln baking:

[0079] The kiln is cooled to 220 degrees and the cooling speed is controlled.

[0080] Preheat at 800 degrees for 24 hours, slowly increase the temperature.

[0081] Heating at 1200 degrees for 12 hours, maintaining uniform temperature rise.

[0082] 72 hours of high temperature grilling at 1450 degrees, the temperature range is 1400 degrees to 1450 degrees.

[0083] Official production:

[0084] After the second kiln baking is completed, glass raw materials are added to enter the formal production stage.

[0085] Summarize:

[0086] The cerium oxide of this embodiment improves the chemical stability and corrosion resistance of the ceramic material, and is suitable for glass furnaces with high temperatures and complex chemical reaction environments.

[0087] Example 3: Complex process of lanthanide rare earth oxide as praseodymium oxide

[0088] step:

[0089] Material preparation:

[0090] A ceramic material doped with 1.5% praseodymium oxide and 1.5% titanium oxide was prepared, and the main components were 55% aluminum oxide, 25% zirconium oxide, and 20% magnesium oxide.

[0091] The ceramic material is finely powdered to a particle size range of 250 mesh.

[0092] Add 3.5% sodium silicate as a binder and mix thoroughly.

[0093] The mixed material was calcined at 1350 degrees for 6 hours and then slowly cooled to room temperature.

[0094] Applying ceramic material:

[0095] Clean the inner surface of the kiln to ensure it is free of dust and oil.

[0096] Apply the ceramic material evenly on the surface of the inner cavity with a thickness of 1 cm and a thickness of 0.5 cm each time.

[0097] After application, allow to dry naturally for 24 hours.

[0098] First time kiln baking:

[0099] Preheat at 800 degrees for 24 hours, slowly increase the temperature to avoid cracks.

[0100] Heating at 1200 degrees for 12 hours, maintaining uniform temperature rise.

[0101] 72 hours of high temperature grilling at 1600 degrees, the temperature range is 1580 degrees to 1600 degrees.

[0102] 12 hours of low temperature grilling at 800 degrees, with a temperature range of 750 to 850 degrees.

[0103] Cooling and secondary kiln baking:

[0104] The kiln is cooled to 180 degrees and the cooling speed is controlled.

[0105] Preheat at 800 degrees for 24 hours, slowly increase the temperature.

[0106] Heating at 1200 degrees for 12 hours, maintaining uniform temperature rise.

[0107] 72 hours of high temperature grilling at 1450 degrees, the temperature range is 1400 degrees to 1450 degrees.

[0108] Official production:

[0109] After the second kiln baking is completed, glass raw materials are added to enter the formal production stage.

[0110] Summarize:

[0111] The praseodymium oxide in this embodiment improves the material's oxidation resistance and high-temperature stability, and is suitable for glass furnaces in extremely high-temperature environments.

[0112] Example 4: Complex process of high thickness coating

[0113] step:

[0114] Material preparation:

[0115] A ceramic material doped with 0.5% lanthanum oxide and 2.5% titanium oxide was prepared, and the main components were 65% aluminum oxide, 20% zirconium oxide, and 15% magnesium oxide.

[0116] The ceramic material is finely powdered to a particle size range of 300 meshes.

[0117] Add 4% potassium silicate as a binder and mix thoroughly.

[0118] The mixed material was calcined at 1500 degrees for 5 hours and then slowly cooled to room temperature.

[0119] Applying ceramic material:

[0120] Clean the inner surface of the kiln to ensure it is free of dust and oil.

[0121] Apply the ceramic material evenly on the surface of the inner cavity, with a thickness of 0.5 cm each time. Repeat multiple applications to a total thickness of 1.5 cm.

[0122] After application, allow to dry naturally for 18 hours.

[0123] First time kiln baking:

[0124] Preheat at 800 degrees for 24 hours, slowly increase the temperature to avoid cracks.

[0125] Heating at 1200 degrees for 12 hours, maintaining uniform temperature rise.

[0126] 72 hours of high temperature grilling at 1550 degrees, the temperature range is 1550 degrees to 1580 degrees.

[0127] 12 hours of low temperature grilling at 800 degrees, with a temperature range of 750 to 850 degrees.

[0128] Cooling and secondary kiln baking:

[0129] The kiln is cooled to 200 degrees and the cooling rate is controlled.

[0130] Preheat at 800 degrees for 24 hours, slowly increase the temperature.

[0131] Heating at 1200 degrees for 12 hours, maintaining uniform temperature rise.

[0132] 72 hours of high temperature grilling at 1450 degrees, the temperature range is 1400 degrees to 1450 degrees.

[0133] Official production:

[0134] After the second kiln baking is completed, glass raw materials are added to enter the formal production stage.

[0135] Summarize:

[0136] This embodiment uses a thicker coating and multiple coating processes to increase the durability and thermal insulation performance of the protective layer, and is suitable for high-temperature glass furnaces that need to be used for a long time.

[0137] Example 5: Complex process of fine powder treatment

[0138] step:

[0139] Material preparation:

[0140] A ceramic material doped with 1% cerium oxide and 1.5% titanium oxide was prepared, and the main components were 60% aluminum oxide, 25% zirconium oxide, and 15% magnesium oxide.

[0141] The ceramic material is finely powdered to a particle size of 300 mesh.

[0142] Add 3% sodium silicate as a binder and mix thoroughly.

[0143] The mixed material was calcined at 1400 degrees for 4 hours and then slowly cooled to room temperature.

[0144] Applying ceramic material:

[0145] Clean the inner surface of the kiln to ensure it is free of dust and oil.

[0146] Apply the ceramic material evenly on the surface of the inner cavity, with a thickness of 0.3 cm each time. Repeat multiple applications to a total thickness of 1 cm.

[0147] After application, allow to dry naturally for 24 hours.

[0148] First time kiln baking:

[0149] Preheat at 800 degrees for 24 hours, slowly increase the temperature to avoid cracks.

[0150] Heating at 1200 degrees for 12 hours, maintaining uniform temperature rise.

[0151] Grill at 1580 degrees for 72 hours, with a temperature range of 1550 to 1580 degrees.

[0152] 12 hours of low temperature grilling at 800 degrees, with a temperature range of 750 to 850 degrees.

[0153] Cooling and secondary kiln baking:

[0154] The kiln is cooled to 200 degrees and the cooling rate is controlled.

[0155] Preheat at 800 degrees for 24 hours, slowly increase the temperature.

[0156] Heating at 1200 degrees for 12 hours, maintaining uniform temperature rise.

[0157] 72 hours of high temperature grilling at 1450 degrees, the temperature range is 1400 degrees to 1450 degrees.

[0158] Official production:

[0159] After the second kiln baking is completed, glass raw materials are added to enter the formal production stage.

[0160] Summarize:

[0161] This embodiment ensures the uniformity and density of the ceramic coating through fine powder processing and multiple coatings, improves the protective effect, and is suitable for glass furnaces with high requirements.

[0162] Summary of Examples

[0163] The above five examples show the effects of different lanthanide rare earth oxides and different process parameters on the performance of ceramic materials. Each example shows its unique advantages in different application scenarios and is suitable for glass kilns with different requirements. By adjusting the type and content of lanthanide rare earth oxides, coating thickness, coating process and kiln parameters, the best optimization of the kiln inner wall protective layer can be achieved.

[0164] Comprehensive test experimental process

[0165] In order to evaluate the comprehensive performance of the five different embodiments, a general test experiment is designed. The test items include:

[0166] High temperature resistance test

[0167] Antioxidant performance test

[0168] Chemical corrosion resistance test

[0169] Mechanical strength test

[0170] Thermal shock stability test

[0171] Specific process of test experiment

[0172] 1. Sample Preparation

[0173] Several ceramic material samples of the same size (each sample is 10 cm x 10 cm x 1 cm) were taken out from each example. Ten samples were prepared for each example, for a total of 50 samples, for different test items.

[0174] 2. High temperature resistance test

[0175] Testing process:

[0176] Two samples of each example were placed in a high temperature furnace.

[0177] Gradually increase the temperature to 1600 degrees and maintain constant temperature for 1 hour.

[0178] After cooling, the mass change and morphological changes of each material were recorded.

[0179] Test data:

[0180] .

[0181] 3. Antioxidant performance test

[0182] Testing process:

[0183] Two samples of each embodiment were placed in an oxygen atmosphere and heated to 1000 degrees, and kept at a constant temperature for 2 hours.

[0184] After cooling, the mass change of each material in the high temperature oxygen atmosphere was recorded.

[0185] Test data:

[0186] .

[0187] 4. Chemical corrosion resistance test

[0188] Testing process:

[0189] Two samples of each example were immersed in a 10% sulfuric acid solution and kept at a constant temperature of 100 degrees for 1 hour.

[0190] The sample was removed, cleaned and dried, and the mass change was measured.

[0191] Test data:

[0192] .

[0193] 5. Mechanical strength test

[0194] Testing process:

[0195] The compressive strength of two samples of each example was measured using a compression testing machine.

[0196] Record the compressive strength value for each material.

[0197] Test data:

[0198] .

[0199] 6. Thermal shock stability test

[0200] Testing process:

[0201] Two samples of each example were kept in a high-temperature furnace at 1000 degrees for 1 hour, and then quickly taken out and placed in cold water, and this process was repeated 10 times.

[0202] The morphological changes and cracking conditions of each material were recorded.

[0203] Test data:

[0204] .

[0205] Test results and summary

[0206] High temperature resistance:

[0207] Examples 1 to 5 all exhibit good high temperature resistance, with quality changes within the allowable range and no significant changes in morphology.

[0208] Antioxidant Properties:

[0209] Example 3 has the best antioxidant performance and the smallest quality change.

[0210] Examples 1 and 4 also exhibited good antioxidant properties.

[0211] Chemical corrosion resistance:

[0212] Example 5 has the best chemical corrosion resistance and the smallest quality change.

[0213] Examples 2 and 4 also exhibit good chemical corrosion resistance.

[0214] Mechanical strength:

[0215] Example 4 has the highest mechanical strength, with an average compressive strength of 130 MPa.

[0216] The mechanical strength of Example 3 is also relatively high, with an average compressive strength of 125 MPa.

[0217] Prior art and technical solutions of the present invention

[0218] Technical Solution

[0219] The commonly used protective layer of the inner wall of glass furnace is mainly composed of traditional refractory bricks and general ceramic coatings. These materials usually contain high content of aluminum oxide (Al2O3) and silicon oxide (SiO2), but do not contain rare earth oxides and other additives, and are usually used below 1500°C.

[0220] Technical solution of the present invention

[0221] The technical solution of the present invention comprises the following steps:

[0222] Material preparation: Trace amounts of lanthanide rare earth oxides (such as lanthanum oxide, cerium oxide, praseodymium oxide) and oxides (such as titanium oxide) are added, and the main components are aluminum oxide, zirconium oxide and magnesium oxide.

[0223] Apply ceramic material: Apply a layer of the above ceramic material with a thickness of about one centimeter evenly on the surface of the inner cavity of the kiln.

[0224] The first kiln baking and the second kiln baking: go through multiple stages of preheating, heating, high temperature baking and low temperature baking.

[0225] Comparative experiment 1: High temperature stability and durability comparison experiment

[0226] Experimental design process:

[0227] Sample preparation: Take several samples of the same size (10 cm x 10 cm x 1 cm) from the prior art and the technical solutions of the present invention. Prepare 10 samples for each technology.

[0228] High temperature treatment:

[0229] Gradually increase the temperature to 1600°C and maintain constant temperature for 2 hours.

[0230] After cooling, the mass change, morphology change, and microstructure change of the samples were recorded (observed by SEM).

[0231] Experimental data:

[0232] .

[0233] Summarize:

[0234] The ceramic material of the present invention exhibits better stability and durability at high temperatures, has little mass change, has no obvious morphological change, and maintains a dense microstructure.

[0235] Comparative experiment 2: Comparative experiment on chemical corrosion resistance and oxidation resistance

[0236] Experimental design process:

[0237] Sample preparation: Take several samples of the same size (10 cm x 10 cm x 1 cm) from the prior art and the technical solutions of the present invention. Prepare 10 samples for each technology.

[0238] Chemical corrosion resistance test:

[0239] The sample was immersed in 10% sulfuric acid solution and kept at a constant temperature of 100°C for 1 hour.

[0240] The sample was removed, cleaned and dried, and the mass change was measured.

[0241] Antioxidant Test:

[0242] The sample was placed in an oxygen atmosphere and heated to 1000°C, and kept at this temperature for 2 hours.

[0243] Record changes in mass.

[0244] Experimental data:

[0245] .

[0246] Summarize:

[0247] The ceramic material of the present invention exhibits significant advantages in terms of chemical corrosion resistance and oxidation resistance, has little quality change, and is more suitable for use in harsh chemical and oxidative environments.

[0248] Comparative experiment 3: Thermal shock stability and mechanical strength comparison experiment

[0249] Experimental design process:

[0250] Sample preparation: Take several samples of the same size (10 cm x 10 cm x 1 cm) from the prior art and the technical solutions of the present invention. Prepare 5 samples for each technology.

[0251] Thermal shock stability test:

[0252] After the sample was kept in a high-temperature furnace at 1000°C for 1 hour, it was quickly taken out and placed in cold water, and this process was repeated 10 times.

[0253] Record the morphological changes and crack conditions of the samples.

[0254] Mechanical strength test:

[0255] The compressive strength of the samples was measured using a compression testing machine.

[0256] Experimental data:

[0257] .

[0258] Summarize:

[0259] The ceramic material of the present invention exhibits significant advantages in thermal shock stability and mechanical strength, has no obvious cracks, has high compressive strength, and is more suitable for environments with high mechanical stress and rapid temperature changes.

[0260] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for preparing an ultra-high temperature inner shell protective layer for the inner wall of a glass furnace, characterized in that: The following steps are involved: Material preparation: preparing a ceramic material doped with trace amounts of lanthanide rare earth oxides and eye oxides; the eye oxide is titanium oxide; Apply ceramic material: evenly apply a layer of the above ceramic material with a thickness of one centimeter on the surface of the inner cavity of the kiln; Initial kiln baking: 24 hours of preheating at 800 degrees, 12 hours of heating at 1200 degrees, 72 hours of high-temperature baking at 1580 degrees, and 12 hours of low-temperature baking at 800 degrees; Cooling and secondary kiln baking: After the kiln is cooled to 200 degrees, it is preheated at 800 degrees for 24 hours, heated at 1200 degrees for 12 hours, and baked at 1450 degrees for 72 hours; Formal production: After the secondary kiln baking is completed, glass raw materials are added to enter the formal production stage; the amount of lanthanide rare earth oxide added is 0.5% to 2% of the total weight of the ceramic material, and the amount of titanium oxide added is 1% to 3% of the total weight of the ceramic material; The main components of the ceramic material are aluminum oxide, zirconium oxide and magnesium oxide. In the step of applying the ceramic material, the thickness of the ceramic material is 0.5 cm to 1.5 cm; the content of aluminum oxide is 50% to 70%, the content of zirconium oxide is 20% to 30%, and the content of magnesium oxide is 10% to 20%; In the step of preparing the ceramic material, a binder is added, and the type of the binder is sodium silicate or potassium silicate; the amount of the binder added is 3% to 5% of the total weight of the ceramic material, and the binder is fully stirred during the mixing process; In the preparation step of the ceramic material, a high-temperature calcination treatment is performed, and the calcination temperature ranges from 1300 degrees to 1500 degrees.

2. The process for preparing the ultra-high temperature resistant inner shell protective layer for the inner wall of a glass furnace according to claim 1, characterized in that: The ceramic material needs to be finely powdered before being applied, with a particle size range of 200 to 400 meshes. The ceramic material needs to be applied multiple times, with each application having a thickness of 0.2 cm to 0.5 cm.

3. The process for preparing the ultra-high temperature resistant inner shell protective layer for the inner wall of a glass furnace according to claim 1, characterized in that: After the ceramic material is applied, it needs to be dried naturally, and the drying time is 12 to 24 hours.